Determinants of Female Workers’ Wages in Indonesia, 2020–2024 - Rohmah, Yulia Nuur; Anas, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Indonesian female workers still face gender inequality in the labor market, which is reflected in the low wages they receive despite their relatively high levels of productivity. This study aims to estimate the effects of female workers, female labor productivity, females’ years of schooling, and female’s life expectancy on female workers' wages in Indonesia from 2020 to 2024 a panel data regression method with a Fixed Effects Model (FEM) approach. The data was obtained from the Central Statistics Agency (BPS) in 34 provinces in Indonesia from 2020 to 2024. The results show that female workers and females’ life expectancy have a positive effect on female workers’ wages. Meanwhile, female worker productivity and females’ mean years of schooling have no effect on female workers’ wages. These findings indicate the importance of strengthening labor policies that support gender equality through expanding formal employment opportunities for women, improving the quality of women's health and education, strengthening protection for female workers and implementing a fairer wage system without gender discrimination in order to sustainably improve the welfare of female workers in Indonesia.